Numerical simulation of 3-D flow around sounding rocket in the lower thermosphere - J. Kurihara; K.-I. Oyama; N. Iwagami; T. Takahashi (Annales Geophysicae, 2006)
Numerical simulations using the Direct Simulation Monte Carlo (DSMC) method are known to be useful for analyses of aerodynamic effects on in-situ rocket measurements in the lower thermosphere, but the DSMC analysis of a spin modulation caused by an asymmetric flow around the rocket spin axis has been restricted to the two-dimensional and axially symmetric simulations in actual sounding rocket experiments. This study provides a quantitative analysis of the spin modulation using a three-dimensional (3-D) simulation of the asymmetric flow with the DSMC method. Clear spin modulations in the lower thermospheric N2 density measurement by a rocket-borne instrument are simulated using the rocket attitude and velocity, the simplified payload structure, and the approximated atmospheric conditions. Comparison between the observed and simulated spin modulations show a very good agreement within 5% at around 100km. The results of the simulation are used to correct the spin modulations and derive the absolute densities in the background atmosphere.